Transfer of ownership in international sales of goods - Laemmli, Thomas (Intellectual Property Research Unit, 2014)
This thesis deals with how ownership is transferred in connection with international sale contracts. It shows what stumbling blocks might be avoided by observing peculiarities of the law applicable to an international sales contract and especially to the transfer of ownership. Thereby, the following legal systems will be taken into consideration: Lex Mercatoria, Swiss Law, South African Law and English Law. The aim of every domestic and international sales contract is to pass the property of goods from one contract party to the other contract party against the payment of a certain price. Contracts of sales whether written, oral or simple because of a conclusive behaviour are always the basis for transfer of ownership. Every international sales contract is governed by a particular national law or by the so called Lex Mercatoria. Since it is in the parties' autonomy to choose the law governing the contract (freedom of choice) it is critical to know what consequence this choice has on transferring the property, or whether this choice has a consequence at all. International sales contracts mean contracts where parties of different countries are involved. Internationality is defined in Article 1 (1) of the United Nations Convention on Contracts for the International Sale of Goods (hereinafter: CISG) as: "This convention applies to contract of sales of goods between parties whose places of business are in different states" . The obligations of the seller and the buyer are stated in Article 30 and 53 CISG. "The seller must deliver the goods, hand over any documents relating to them and transfer the property as required by the contract and this Convention." "The buyer must pay the price for the goods and take delivery of them as required by the contract and this Convention". Section 2 (1) of the English Sale of Goods Act 1979 defines a contract for the sale of goods as: " a contract by which the seller transfers or agrees to transfer the property in goods to the buyer for a money consideration, called the price." Article 184 Section 1 of the Swiss Code of Obligations (CO) states the following: "A contract of sale is a contract whereby the seller obligates himself to deliver to the buyer the object of purchase and to transfer title thereto to the buyer, and the buyer obligates himself to pay the purchase price to the seller". In South Africa there is obviously no specific act on the sales of goods. Therefore, the requirements for a valid contract have to be derived from common law. Hackwill states that a sales contract is a mutual contract for the transfer of possession of an object in exchange for a price. As mentioned above the contract between seller and buyer is always the basis for the transfer of ownership. However, how the ownership finally transfers in the mentioned legal systems will be established below. All of the mentioned systems of law are more or less based on Roman Law which established the parameters/rules for property law. South African's law of property, sales, and contracts as well as English and Swiss Law can be traced back to Roman Law. Examining this common background by tracing the conceptualization of transfer of ownership in the Roman Property Law will illustrate the extent to which the rules on the transfer of property have evolved since the classical era in order to meet changing needs of modern legal systems.